A educação para sexualidades no ensino médio nas escolas públicas estaduais do Ceará – uma análise do componente curricular: núcleo de trabalho, pesquisa e práticas sociais - Martins, Luana Vanessa Barbosa (2023)
There is an apparent desexualization in the school space, but sexualities are present daily in all social spaces in scenes, gestures, words, events, relationships and, above all, in our existence. However, there are some projects and programs that go against this process of denying sexualities. One of them takes place in state schools in the state of Ceará, Brazil, specially in the Center for Work, Research and Social Practices (NTPPS), the focus of this research. The general objective of this work is to investigate how sexuality education is present in high school education in state schools in Ceará through the NTPPS curricular component. Initially, in order to establish the stateoftheart of such issue, academic works with the same theme were selected; it could be established that, despite the increase of the number of works about such topics, there is still little research on this focus, which highlights the importance of the present research. The methodological processes involved the documentary analysis of the Brazilian National Common Curricular Base (BNCC) and the Ceará Curricular Reference Document (DCRC); analysis of the teaching material that guides the NTPPS program and semistructured interviews with the head of Ceará Education Department and state teachers who teach the program. To treat the collected data, Bardin's thematic content analysis (1979) was used. As a result, it was observed that the BNCC showed no concern with such area of education, not presenting specific strategies or any mention of sexualities on it, as well as the removal of key terms of such theme, which was present in previous versions of the document; the theme was referred together with general aspects of social studies such as human rights and combating prejudice. The DCRC brings a specific discourse about these subjects, with clear terms and objectives, being an advance in such perspective, and showing the interest of the Secretary of Education of the State of Ceará in creating strategies that aim to discuss education for sexualities in a wider way. The NTPPS material and the interviews indicated that, despite its challenges, the Center has configured itself as a space to work on sexualities, both in their biological concepts and social aspects, through its active methodology, and the link between the entire school community that ends up being created within the program, educating young people to live their sexualities in a safe, responsible and healthy way, debating these subjects in a natural and informative way, breaking taboos, so that in addition to becoming protagonists of their stories, they can revolutionize their means, achieving the comprehensive training that Education claims to aim for.